Determinants of Pregnant Women Participation on Triple Elimination of HIV, Syphilis, and Hepatitis B, in Semarang - Fatimah, Mei (Journal of Health Promotion and Behavior, 2020)
Background: HIV, Syphilis, and Hepatitis B infections are very susceptible to transmission from mother to child during pregnancy, childbirth, and breastfeeding. In 2014, the World Health Organisation (WHO) established a list of validation criteria to facilitate efforts of elimination of mother-to-child transmission (EMTCT) of HIV and syphilis. This study aimed to analyze determinants of pregnant women participation in the triple elimination uptake.Subjects and Method: This was a cross sectional study conducted at 25 Public health centers, in Semarang District, Central Java, from December 2019 to February 2020. A sample of 200 pregnant women was selected by random sampling. The dependent variable was triple elimination. The independent variables were intention, access to information, knowledge, outcome expectation, modeling, distance, self-efficacy, and husband support. Community health center was variable in level 2. The data were collected by questionnaire and analyzed by a multiple logistic multilevel analysis.Results: Triple elimination participation in pregnant women increased with good access to information (b= 1.76; 95% CI= 16.72 to 102.18; p<0.001), good knowledge (b= 2.09; 95% CI= 10.91 to 56.14; p<0.001), positive outcome expectation (b= 2.03; 95% CI= 12.93 to 71.91; p<0.001), strong modeling (b= 2.03; 95% CI= 2.83 to 1.64, p< 0.001), strong intention (b= 2.43; 95% CI= 8.49 to 46.22; p <0.001), strong self-efficacy (b= 2.48; 95% CI= 12.64 to 72.37; p<0.001), and strong husband support (b= 1.97; 95% CI= 12.2 to 65.24; p <0.001). Triple elimination participation in pregnant women decreased with further distance to health center (b= -2.20; 95% CI= 0.41 to 1.38; p= 0.032). Public health center had contextual effect on the participation of triple elimination in pregnant women with ICC= 40.64%.Conclusion: Triple elimination participation in pregnant women increases with good access to information, good knowledge, positive outcome expectation, strong modeling, strong intention, strong self-efficacy, and strong husband support. It decreases with further distance to health center. Public health center has contextual effect on the participation of triple elimination in pregnant womenKeywords: triple elimination, HIV, Syphilis, Hepatitis B, multilevel analysisJournal of Health Promotion and Behavior (2020), 5(2): 124-134https://doi.org/10.26911/thejhpb.2020.05.02.07